하이브리드 L-PBF 적층 제조 공정의 조형 특성 평가 - 이필호(Pil-Ho Lee); 송여울(Yeo-Ul Song); 김용래(Yongrae Kim); 허세곤(Segon Heo); 이창우(Chang-Woo Lee) (한국생산제조학회지, 2023)
In this study, the integration of hybrid laser-powder bed fusion (L-PBF) technology in STS316L manufacturing, combining L-PBF and milling processes, was investigated. A hybrid L-PBF system was developed to explore various process variables, such as laser output, scan speed, and hatching interval. It was determined that energy density is crucial for realizing a specimen’s relative density exceeding 99.5%. Milling experiments revealed insights from the L-PBF process characterization, including the emergence of defects in radial cutting depth and improved surface quality in axial cutting depth with increased depth. This research has the potential to revolutionize component fabrication in industries such as defense, medical care, mold making, and aerospace. The integration of hybrid L-PBF and milling processes offers enhanced precision and superior surface quality in STS316L stainless steel component production, meeting diverse application demands. KCI Citation Count: 0